The modern history of Japan - Beasley, William Gerald (Weidenfeld and Nicolson, 1978)
When European explorers of the sixteenth century rounded the Malay peninsula and moved into Far Eastern waters they confronted a civilization quite different from those which they had found in India and western Asia. Over an area extending from Tongking in the south to Korea in the north they met with a culture which was in origin Chinese, its members looking to China as the heart of their international structure and the source of their dominant beliefs. It was not an entirely uniform culture, for the degree and nature of Chinese influence had varied with both time and place. Nevertheless the differences between one part of the region and another were no greater than those to be found within the boundaries of Europe, certainly not great enough to make invalid the application of a common label to the whole...